1990
DOI: 10.1111/j.1530-0277.1990.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Hypoxemia Is Increased in Abstaining Chronic Alcoholic Men

Abstract: Previously we reported that abstaining chronic alcoholic men demonstrated significantly more nighttime hypoxemia than a control group. Here, we report a replication employing a larger sample of abstaining chronic alcoholics and a more appropriate control group than that used in the previous study. Forty-seven males, 48.4 +/- 1.7 years of age (mean +/- SEM), reporting 24.8 +/- 1.5 years of heavy alcohol use, comprised the abstaining alcohol group. Thirty-five age- and weight-matched males, 50.3 +/- 1.7 years we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
4
1
1
Order By: Relevance
“…Furthermore, case reports indicate that treating sleep apnea may improve psychotic symptoms. 9 An association between sleep apnea and substance and alcohol abuse has been reported; [35][36][37][38][39][40] however, we did not find an increased prevalence of substance abuse in the apnea group (3.32%) compared with the non-apnea group (3.28%). The prevalence for alcohol dependence in VHA beneficiaries is reportedly high (11%); 12 however, in our study, the prevalence was only 5.68% in the general VHA population and 5.53% in subjects with sleepapnea diagnoses.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, case reports indicate that treating sleep apnea may improve psychotic symptoms. 9 An association between sleep apnea and substance and alcohol abuse has been reported; [35][36][37][38][39][40] however, we did not find an increased prevalence of substance abuse in the apnea group (3.32%) compared with the non-apnea group (3.28%). The prevalence for alcohol dependence in VHA beneficiaries is reportedly high (11%); 12 however, in our study, the prevalence was only 5.68% in the general VHA population and 5.53% in subjects with sleepapnea diagnoses.…”
Section: Discussioncontrasting
confidence: 58%
“…Apart from the acute effects of alcohol ingestion, it has been shown that long-term alcohol ingestion may be important in the pathogenesis of sleep apnea, i.e. abstaining alcoholics have an increased frequency of apneas and hypopneas (7,8). In previous studies (9,10) in which questionnaires were used to evaluate the alcohol consumption of OSAS patients, their consumption was found to be no higher than that of the general population.…”
Section: Introductionmentioning
confidence: 95%
“…Typical sleep disturbances include difficulties falling asleep (sleep latency) and a reduction in the total amount of time in bed spent sleeping (sleep efficiency) (Brower, 2001;Landolt and Gillin, 2001). Specific sleep disorders, such as sleep apnea, may also occur at a higher rate among individuals with alcoholism, which also may contribute to sleep disruption (Le Bon et al, 1997;Vitiello et al, 1990). Even after remission of alcoholism, sleep disturbances frequently persist for months to possibly a few years, and sleep patterns may normalize with extended periods of remission (Currie et al, 2003;Drummond et al, 1998;Williams and Rundell, 1981).…”
mentioning
confidence: 99%